Multiple Myeloma Outpatient Transplant Program in the Era of Novel Agents: State-of-the-Art - Martino, Massimo; Paviglianiti, Annalisa; Memoli, Mara; Martinelli, Giovanni; Cerchione, Claudio (Frontiers in Oncology, 2020)
Introduction: Multiple myeloma (MM) is the most common indication for autologous stem cell transplantation (ASCT) and Outpatient models have been widely developed in this setting. Expert opinion: Although numerous studies have demonstrated the safety and feasibility of outpatient ASCT, it has yet to be established as a routine procedure. Stringent guidelines for patient selection and clinical management including functional status, caregiver support, and psychological aspects are critical to identify the patients who are most likely to benefit. However, there is still no general agreement on these criteria. Quality of life data are limited and contradictory. There is considerable variability in outpatient transplant models and data do not support a preference for one delivery model over another. Survival and other transplant-related outcomes have not been widely reported. The procedure is cost-effective within the context of a hospital budget but an in-depth analysis of the real cost of these programs has yet to be performed.